PENGEMBANGAN SISTEM INFORMASI ABSENSI CAFFE LIYANE KOPI BERBASIS WEB MENGGUNAKAN MODEL AGILE - Alamsyah, Ramadhan; Alzaki, Faiz Zakwan; Sanusi, Muhammad Tri Bintang; Hayono, Wasis (GATOTKACA Journal (Teknik Sipil, Informatika, Mesin dan Arsitektur), 2025)
Caffe Liyane Kopi is a food and beverage business that faces challenges in managing employee attendance due to the continued use of manual record-keeping with logbooks. This method presents various limitations, including data entry errors, difficulty in tracking attendance history, and vulnerability to data manipulation. To address these issues, a web-based attendance information system was developed using the Agile methodology with a Scrum approach. The development process was carried out through five sprint cycles covering planning, development, testing, and feature refinement stages. The tools used include PHP, MySQL, HTML, CSS, and supporting libraries for QR Code .The development results show that the system successfully handles login processes, session creation, QR Code scanning, and automatic attendance recording. A face recognition feature was also integrated to enhance security. The system provides real-time attendance reports that support managerial decision-making. Testing demonstrated high success rates, and users expressed satisfaction with the system’s usability. In conclusion, the developed system successfully replaces the manual method with a more efficient and accurate digital solution and holds potential for further development to meet evolving business needs.